Peranan Perhitungan Harga Pokok Produksi Pendekatan Full Costing Dalam Menentukan Harga Jual Dengan Metode Cost Plus Pricing : Studi Kasus pada Industri Olahan Tahu Nono Purnomo - Annissa Fikri (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The purpose of this study was to determine the role of calculating the cost of production and determining the selling price of shoes in Processed Tofu Industry Mr. Nono Purnomo. To find out how big the difference is in determining the cost of production using the company method and the full costing approach and to compare selling prices according to the company's method using the Cost Plus Pricing method. The type of research used is qualitative research. The analytical method used in this research is descriptive qualitative analysis. The data used in this research is secondary data. The data were obtained from previous research that had been carried out by Efendi Yanto et al. directly with Processed Tofu Industry Mr. Nono Purnomo and data in the form of production cost information such as raw material costs, labor costs, and tofu factory overhead costs during 2020. In addition, additional secondary data is obtained from intermediary media such as books or literature, journals related to research titles, and also via the internet. The results of the study can be concluded that the calculation of the cost of production according to Processed Tofu Industry Mr. Nono Purnomo lower than the calculation of the cost of production using the full costing method. Total cost of production according to Processed Tofu Industry Mr. Nono Purnomo is Rp. 267.577.000 or Rp. 24.773/board. While the selling price using the full costing method Rp. 313.634.560 or Rp. 29.038/board. This is due to factory overhead costs that are not taken into account by Processed Tofu Industry Mr. Nono Purnomo like depreciation costs, indirect labor costs, electricity costs, and maintenance costs for factory machinery and vehicles. Setting the selling price must be appropriate because setting a selling price that is too high will result in difficulty competing with similar products while setting a selling price that is too low will result in reduced revenue generated by Processed Tofu Industry Mr. Nono Purnomo. The difference in determining the cost of production will affect Processed Tofu Industry Mr. Nono Purnomoo in determining the selling price, because the cost of production is the main element in determining the selling price. Calculation of the total selling price according to Processed Tofu Industry Mr. Nono Purnomois Rp. 383813.000 or Rp. 35,532/ board. Meanwhile, the selling price uses the Cost Plus Pricing method, which is Rp. 449.878.000 or Rp. 41.652/board.